Dietary adequacy and alcohol consumption of Inuvialuit women of child‐bearing age in the Northwest Territories, Canada. Issue 6 (10th April 2013) - Kolahdooz, F.; Spearing, K.; Corriveau, A.; Sharma, S.
Abstract Background Previous studies highlight a possible association between alcohol‐drinking patterns and dietary inadequacies, which may have negative implications, particularly for women of child‐bearing age. The present study aimed to compare dietary adequacy among alcohol drinkers versus nondrinkers in Inuvialuit women of child‐bearing age. Methods A cross‐sectional survey of 92 randomly selected women of childbearing age (19–44 years) was conducted in three communities in the Northwest Territories of Arctic Canada, using a validated quantitative food frequency questionnaire. Data were analysed to compare mean daily energy and nutrient intakes, dietary adequacy and nutrient densities (per 4184 kJ) between alcohol drinkers and nondrinkers, as well as heavy drinkers and nonheavy drinkers, using the nonparametric Wilcoxen rank sum test. Results The response rate was between 65% and 85% depending on the community sampled. Of the study participants, 54% (n = 49) were drinkers and 46% (n = 42) were nondrinkers. Of the drinkers, 45% (n = 22) were heavy drinkers. Mean energy intakes were high among all women, although they were significantly higher among drinkers [17 179 kJ (4106 kcal)] compared to nondrinkers [13 317 kJ (3183 kcal)]. There were no significant differences in nutrient intake between the two groups; however, drinkers had a lower nutrient density for most nutrients. Heavy drinkers had a significantly lower nutrient density for all nutrients, except protein, iron, and vitamins B6, C and D, compared to nonheavy drinkers. Conclusions The findings of the present study provide evidence of inadequate dietary intake among Inuvialuit of child‐bearing age, regardless of alcohol‐drinking behaviour.